Meningkatkan Pengetahuan Gizi Seimbang untuk Anak 1-6 Tahun Melalui Penyuluhan pada Orang Tua - Hastuti, Eka Puji; Setiasari, Ria; Oktariani, Liana (Ridwan Institute, 2021)
The purpose of this study is to know the level of knowledge of parents about balanced nutrition in order to increase parental awareness about the importance of balanced nutrition, especially in children aged 1 to 6 years. This study uses a qualitative approach in which an analysis of how far parents know about the concept of balanced nutrition. The results of this study show that there is still a lack of knowledge and understanding of parents about the importance of balanced nutrition that includes components of calories, proteins, fats, vitamins, minerals and water so that the usual food menu served to their children is still far from balanced nutritional standards. Nutritional insufficiency in children can have a serious impact on the growth and development of children such as decreased endurance, growth disorders and decreased concentration of learning in children who begin to enter school age. Therefore, every parent needs to understand and apply the concept of balanced nutrition in daily life so that the risk of impacts that may arise from nutritional insufficiency in children can decrease